Profesionalisme Guru Dalam Pembelajaran PKN di SD Al-Mukmin Medan - Abdulgani Jamora Nasution; Fitri Kholilah Nasution; Miftahul Husna; Nisa Amelia Purba (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
This research was conducted with the aim of knowing how the professionalism of teachers in PKN learning at SD Al-Mukmin Medan. The existence of professional and competent teachers is a non-negotiable necessity to facilitate the achievement of learning demands and goals in schools. Professional teachers will be able to reflect their teacher's figure with broad insight and have a number of competencies that support their duties. This research was conducted at Al-Mukmin Elementary School in Medan which is located on Jalan Benteng Hilir, Tembung, Kec. Percut Sei Tuan, Deli Serdang Regency, North Sumatra. Held for 1 day. This research is categorized as a qualitative descriptive research that applies research steps that produce descriptive data in the form of written words. The results of the study show that teacher professionalism in PKN learning is teacher professionalism in PKN learning is that teachers read books about education, read and write scientific papers, follow actual news from the media, attend training, attend KKG, teachers conduct classroom action research, teachers are also active in organizations . Keywords: Teacher Professionalism, Internship Learning in Elementary School.